Integration of thermal insulation material and active moving air cavity ventilation in a cool roof system for attic temperature reduction - Tan, Kai Feng (2022)
The roof is the primary heat source for landed buildings since it is exposed to the sun. This will lead to significant heat gain in the attic, causing thermal discomfort for the indoor dwellers and increasing cooling loads. A cool roof system can provide thermal insulation to the attic, preventing excessive heat gain and lowering the cooling load, saving electricity consumption from air conditioning systems. Thus, cool roofs' attic temperature reduction performance with passive thermal insulation and active ventilation components, including vegetation layer, lightweight foam concrete (LFC) roof slab of density 1250 kg/m3 , and active moving air cavity (MAC) with solar-powered fans (S-P Fs) are studied. Five roof models were built applying these elements in stages, with the first model as a reinforced concrete roof to be the base model. All roof models were inclined at 30°. The experiment was conducted indoors by projecting two 500 W halogen spotlights right angle at each roof model, and the temperature at the ambient, roof surface, attic, and MAC was measured with ktype thermocouples for 30 minutes, and the variation was shown in a plot of temperature versus times for each roof model. The temperature cooling performance of each model was compared against the predecessor design and base model. A significant drop in attic temperature increment was observed when the MAC was installed under the LFC roof slab, with a maximum attic temperature of 28.9 °C and an average increment rate of 0.05 °C/min, 50% slower than the previous roof model. When the vegetation layer and S-P Fs were added, the temperature in the attic was almost maintained at a constant level of 26.9 °C with a rate of 0.003 °C/min, which is a staggering 96.77% lower than the based model. In brief, this experiment outcome showed the effectiveness of the cool roof system integrating a vegetation layer, LFC, and an active MAC in keeping the attic cool.